PENDUGAAN CADANGAN KARBON PADA TEGAKAN EUCALYPTUS IND 47 UMUR 5 TAHUN DI IUPHHK PT.TOBA PULP LESTARI, Tbk. SEKTOR TELE - Ansencia Manullang; Muhdi Muhdi; Kansih Sri Hartini (Peronema Forestry Science Journal, 2016)
Forest can reduce levels of carbondioxide (CO2) in the air and store it as organic matter in biomass plants. This research aimed to estimate the potential of biomass and carbon of Eucalyptus IND 47 that was  5 years old at IUPHHK PT. Toba Pulp Lestari, Tbk. Tele Sector. The method used in this study is a destructive method. Implementation of research activities carried out in two stages, namely field data collection and analyze biomass and carbon of the parts of stands in laboratory. Parameter measured in the field is wet weight while the measured parameter in laboratory were moisture content, volatile matter content, ash content, and carbon content. The result showed the best allometric equations for mass content of biomass and carbon in stands of Eucalyptus IND 47  was W = 454.419 – 45.528D + 1.886D2 and C = 220.979 – 23.389D + 1.004D2.. The potential of biomass and carbon stocks in stands of Eucalyptus IND 47  at IUPHHK PT. Toba Pulp Lestari, Tbk. Tele Sector is 243.18 tons/ha  and 118.89 C tons/ha. Keywords : 5 years old of Eucalyptus IND 47, biomass, carbon